Manajemen Konservatif Abses Payudara Masa Nifas melalui Asuhan Berkesinambungan di Puskesmas PONED: Laporan Kasus - Pipit Indra L; Thania Maharani Somantri (MEJORA Medical Journal Awatara, 2026)
Comprehensive midwifery care is a holistic, continuous, evidence-based, and woman-centred model of care covering pregnancy, childbirth, the postpartum period, the newborn, and family planning. This study aimed to describe the implementation of comprehensive midwifery care for Mrs. D, a 36-year-old G3P1A1 woman, at UPTD Babakan Public Health Centre, Cirebon Regency, in 2026. A descriptive case study design with a continuity of care approach was used. Data were collected through interviews, physical examinations, observation, and documentation of the maternal and child health book and medical records, and were documented using the SOAP method. Care was provided from 33 weeks of gestation until 41 days postpartum and was analysed by comparing field practice with midwifery care standards. The results showed that antenatal care met the standard of six visits with complete 12T services; labour progressed spontaneously and physiologically within four hours with an estimated blood loss of 60 cc; the newborn was male, weighing 2500 grams, with an Apgar score within normal limits. At the third postpartum visit (day 10), an early-stage localized left breast abscess was identified. The case was managed conservatively in collaboration with the primary health center physician through the administration of oral antibiotics (Amoxicillin 500 mg three times daily for 7 days), health education (IEC) on proper breastfeeding techniques, warm and cold compresses, regular breast emptying, and breast massage. Evaluation on day 41 showed that the breast condition had improved with complete absorption of the abscess, uterine involution was complete, and no further complications were observed. Comprehensive midwifery care utilizing a continuity of care approach proved to facilitate early detection and management of breastfeeding complications during the postpartum period.